Health system barriers and enablers to early access to breast cancer screening, detection, and diagnosis: a global analysis applied to the MENA region. (November 2017) - Bowser, D.; Marqusee, H.; El Koussa, M.; Atun, R.
Abstract: Objectives: To identify barriers and enablers that impact access to early screening, detection, and diagnosis of breast cancer both globally and more specifically in the Middle East and North Africa (MENA) region (with a specific focus on Egypt, Jordan, Oman, Saudi Arabia, United Arab Emirates [UAE], and Kuwait) with a specific focus on the health system. Study design: A systematic review of literature. Methods: We conducted a systematic reviewing using the PRISMA methodology. We searched PubMed, Global Index Medicus, and EMBASE for studies on 'breast cancer', 'breast neoplasm, ' or 'screening, early detection, and early diagnosis' as well as key words related to the following barriers: religion, culture, health literacy, lack of knowledge/awareness/understanding, attitudes, fatalism/fear, shame/embarrassment, and physician gender from January 1, 2000 until September 1, 2016. Two independent reviewers screened both titles and abstracts. The application of inclusion and exclusion criteria yielded a final list of articles. A conceptual framework was used to guide the thematic analysis and examine health system barriers and enablers to breast cancer screening at the broader macro health system level, at the health provider level, and the individual level. The analysis was conducted globally and in the MENA region. Results: A total of 11, 936 references were identified through the initial search strategy, of which 55 were included in the final thematic analysis. The results found the following barriers and enablers to access to breast cancer screening at the health system level, the health provider level, and the individual level: health system structures such as health insurance and care coordination systems, costs, time concerns, provider characteristics including gender of the provider, quality of care issues, medical concerns, and fear. In addition, the following seven barriers and enablers were identified at the health system or provider level as significantly impacting screening for breast cancer: (1) access to insurance, (2) physician recommendation, (3) physician gender, (4) provider characteristics, (5) having a regular provider, (6) fear of the system or procedure, and (7) knowledge of the health system. More specifically, the largest increased odds for having a mammogram was from having insurance, having a physician recommendation, type of provider (mainly gynecologist), and having regular contact with a physician. Clinical breast examinations were increased by having insurance and having regular contact with a physician. The eight studies identified from the MENA region identified barriers to breast cancer screening related to service quality, fear of pain and of cancer itself, female versus male provider, having a physician recommend the screen, cost issues as well as time and convenience of the services. Conclusions: There are a number of system changes that can be made to remove barriers to breast cancer screening. Some of these system changes apply directly to MENA countries. A larger health system assessment of a country is warranted to determine which health system changes should be made to most efficiently and effectively improve access to breast cancer screening. Highlights: Health system analyses are needed to identify barriers/enablers to breast cancer care. Health system assessments are needed globally and in the MENA region. Having health insurance and a gynecologist are positively correlated with mammograms. Strengthening health systems at all level is the key to improving breast cancer care.